Gordon Carruthers, Hans Birkigt and Ernst Feuereisen - (Author); (Interviewer); (Publisher) (1930)
Photograph - Three men and a dog on a scow at Pelican Portage, Alberta. Left to right: Gordon Carruthers, Hans Birkigt, Ernst Feuereisen